Development and Implementation of a Locally Produced Ready-to-Use Therapeutic Food (RUTF) in Vietnam. (June 2014) - Phuong, Huynh; Nga, Tran Thuy; Mathisen, Roger; Nguyen, Marie; Hop, Le Thi; Hoa, Do Thi Bao; Minh, Hong Nguyen; Tuyen, Le Danh; Berger, Jacques; Wieringa, Frank Tammo
Background: In Vietnam, malnutrition remains a public health problem, even though much progress has been made in the last decades. The number of cases of severe acute malnutrition (SAM) is more than 200, 000 per year. To accelerate the treatment of SAM, community-based treatment with ready-to-use-therapeutic foods (RUTFs) is preferred. However, a locally available and acceptable RUTF for the treatment of SAM was lacking. Objective: In a joint effort by the National Institute of Nutrition, UNICEF, and the Institut de Recherche pour le Développement, a local RUTF was developed and tested. Methods: The product was optimalized for impact and acceptability. At the same time, capacity for the Integrated Management of Acute Malnutrition (IMAM) was developed. Results: The local product was found to be highly acceptable and effective. After training of health staff, the product could be introduced in the IMAM program. Conclusions: The IMAM program was highly successful in treating children with SAM, with more than 90% of the children recovering. Production capacity of the factory is currently being increased to enable up-scaling of the IMAM program and potential export of the product to countries in the region.